Investigating the Cryptocurrency Market and its Impact on Financial Institutions - Rangi, Simranraj Kaur (2021)
The cryptocurrency market has seen lots of growth and attention over the last few years with many tipping digital coins to be the future of currency. Decentralising currency is a relatively new phenomenon which leaves individuals sceptical of how risky and volatile these cryptocurrencies are. This dissertation aims to investigate the cryptocurrency market using the Prophet method and the GARCH model in R to explore the returns and volatilities of Bitcoin, Ethereum and Dogecoin. Additionally, the impacts of the cryptocurrency market on financial institutions will be explored.